Atmospheric new particle formation and growth: review of field observations - Veli-Matti Kerminen; Xuemeng Chen; Ville Vakkari; Tuukka Petäjä; Markku Kulmala; Federico Bianchi (Environmental Research Letters, 2018)
This review focuses on the observed characteristics of atmospheric new particle formation (NPF) in different environments of the global troposphere. After a short introduction, we will present a theoretical background that discusses the methods used to analyze measurement data on atmospheric NPF and the associated terminology. We will update on our current understanding of regional NPF, i.e. NPF taking simultaneously place over large spatial scales, and complement that with a full review on reported NPF and growth rates during regional NPF events. We will shortly review atmospheric NPF taking place at sub-regional scales. Since the growth of newly-formed particles into larger sizes is of great current interest, we will briefly discuss our observation-based understanding on which gaseous compounds contribute to the growth of newly-formed particles, and what implications this will have on atmospheric cloud condensation nuclei formation. We will finish the review with a summary of our main findings and future outlook that outlines the remaining research questions and needs for additional measurements.